Loosening detection of the femoral component of hip prostheses with extracorporeal shockwaves: A pilot study. Issue 2 (February 2015) - Rieger, Johannes S.; Jaeger, Sebastian; Kretzer, Jan Philippe; Rupp, Rüdiger; Bitsch, Rudi G.
Highlights A non-invasive and non-radiological vibrational method was proposed to analyze the fixation of total hip endoprostheses. For excitation, an innovative approach using extracorporeal shockwaves was assessed. The results showed an interrelation between the state of loosening of the implant and the resonance frequency of the bone-implant compound. With this technique the degree of stem loosening could be determined in a soft tissue considering configuration.